Application of Dynamic Structural Model to Identify Factors That Influence Capital Adjustments in The National Manufacturing Industry - Harsono, Iwan; Jusatria; Indrapraja, Rachmadi; Henri Kusnadi, Iwan; Rohman, Saeful (Jurnal Informasi dan Teknologi, 2024)
This research aims to determine the costs of capital adjustments and company dynamics. Company panels comprise the database. The main advantage of analyzing the nature of adjustment costs at the plant level is that the data contain information for purchases and sales of capital goods. Panel data, including information from many plants and long periods, allows for a more comprehensive analysis of firms' investment behavior in the face of capital adjustment costs. The estimation results allow for the recovery of companies' frictions in adjusting their capital stock. The estimation results for capital adjustment costs are consistent with other studies using similar methodologies. Estimates show that there are significant, unchangeable fixed costs, as well as moderate quadratic costs. Researchers then use the estimated parameters in a counterfactual simulation to analyze the impact of a decline in average firm profitability on the labor market. The results show a significant labor market response to the shock, with the transition to the new stable state being slow and taking several years to complete the adjustment. The simulations highlight the importance of not only modeling capital mobility but also considering and estimating its frictions to evaluate the impact of policies or shocks on the economy. The mobility and capital adjustment costs influence the speed of the economy's adjustment to shocks and their effects on factor allocation and remuneration in the short and long term.